Effect of treatment duration on the associations between three modern antidiabetic drugs and survival outcomes of lung cancer in China - Chen, Zijia; Wang, Xiaonan; Zhang, Zhongtao; Yang, Lu; Lei, Chao; Di, Yupeng; Huang, Ye; Li, Yan (Frontiers in Molecular Biosciences, 2026)
BackgroundSome antidiabetic drugs have been shown to have tumor suppressor or activator properties. The associations between the treatment durations of three relatively new classes of antidiabetic medications, namely glucagon-like peptide-1 receptor agonists (GLP-1RA), dipeptidyl peptidase 4 inhibitors (DPP-4I), and sodium–glucose cotransporter 2 inhibitors (SGLT-2I), and lung cancer prognosis remain unclear.MethodsA retrospective analysis was conducted on 11,357 newly diagnosed lung cancer patients with type 2 diabetes; these patients were recruited from the National Healthcare Big Data (East) Center and were divided into three groups based on their use of DPP-4I, GLP-1RA, or SGLT-2I, along with categorization of their treatment durations. Cox proportional hazards models were employed to assess the associations between drug duration and survival outcomes, including progression-free survival (PFS) and overall survival (OS). The multivariable models were adjusted for covariates like age, sex, smoking status, biomarkers, and cancer treatments. Sensitivity analyses and Kaplan–Meier estimates were used to validate the findings.ResultsIn terms of the PFS, the highest quartile of GLP-1RA treatment (≥560 days) showed a lower incidence of cancer progression (hazard ratio (HR): 0.43; 95% confidence interval (CI): 0.18, 1.03), although the results were not statistically significant. DPP-4I and SGLT-2I showed less consistent trends. In terms of OS, GLP-1RA demonstrated a linear dose–response characteristic with reduced mortality risk over longer treatment durations, whereas DPP-4I and SGLT-2I showed non-linear associations. The sensitivity analyses confirmed these findings.ConclusionLonger treatment durations of GLP-1RA, SGLT-2I, and DPP-4I reduced the risks of disease progression and mortality in lung cancer patients with type 2 diabetes. Among these drug classes, GLP-1RA showed consistent benefits while DPP-4I and SGLT-2I had non-linear associations, with shorter treatment durations being linked to higher risk.